CO2 adsorption and separation properties of M-MOF-74 materials determined by molecular simulation - Jia Deng; Guangjie Zhao; Lan Zhang; Huizhong Ma; Yan Rong (Capillarity, 2023)
This study simulated the adsorption and separation of CO2 by the metal-organic frameworks material M-MOF-74, established the skeleton model of M-MOF-74 series adsorbent, and calculated the adsorption of CO2 pure component gas and CO2/N2 mixed gas on MMOF- 74 series adsorbent by the grand canonical Monte Carlo method. Among the CO2 adsorption performances of MOF-74 materials with metal centers of Mg, Co, Ni, and Zn, Mg-MOF-74 had the highest CO2 adsorption capacity, adsorption selection coefficient and adsorption heat. When mixed gas was adsorbed, the law of CO2 adsorption was consistent with that of pure CO2 adsorption. The size law of adsorption heat on MOF-74 was similar to that of adsorption amount. Our findings demonstrated that the interaction between the metal-organic framework material and CO2 is greater than that between the material and N2. The interaction between the gas and the MOF-74 series adsorbent was the main factor affecting the adsorption amount, which reveals the strong influence of metal central atoms on the amount of gas adsorption. Our findings provide new ideas for the design of efficient adsorbent materials. Document Type: Original article Cited as: Deng, J., Zhao, G., Zhang, L., Ma, H., Rong, Y. CO2 adsorption and separation properties of M-MOF-74 materials determined by molecular simulation. Capillarity, 2023, 6(1): 13-18. https://doi.org/10.46690/capi.2023.01.02